The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1677/joe.0.1790119
|View full text |Cite
|
Sign up to set email alerts
|

Distribution analysis of vitamin D highlights differences in population subgroups: preliminary observations from a pilot study in UK adults

Abstract: There is no consensus between authors on the definition of a replete or deficient vitamin D state. Our aim was to describe a suitable method that could be used to compare vitamin D data in subject groups with small or large numbers.Two hundred and forty indigenous asymptomatic, non-pregnant adult subjects recruited from a singleconsultation outpatient attendance with normal biochemistry, represented a sample of our inner city district population. 25-hydroxyvitamin D (25,OHD 3 ) levels were measured to illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 41 publications
(29 reference statements)
3
36
0
Order By: Relevance
“…The study was conducted during summer, and values of 25(OH)D are expected to be even lower during winter on the basis of the literature (Chapuy et al, 1996;Goswami et al, 2000;Pal et al, 2003;Pasco et al, 2004). Natural foods rich in vitamin D are not commonly consumed by the larger population, and there are no governmental regulations that (Maalouf et al, 2007), but there remain no guidelines for younger women and for children.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted during summer, and values of 25(OH)D are expected to be even lower during winter on the basis of the literature (Chapuy et al, 1996;Goswami et al, 2000;Pal et al, 2003;Pasco et al, 2004). Natural foods rich in vitamin D are not commonly consumed by the larger population, and there are no governmental regulations that (Maalouf et al, 2007), but there remain no guidelines for younger women and for children.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency was reported in up to 94% of an Asian cohort in Birmingham, UK. 6 Although Liverpool does not have a large BME population, vitamin D deficiency has been noted as a health issue in its Somali community since 2003. 7,8 Consequently, the frequency of vitamin D testing is increasing, particularly in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 In the UK, reduced levels of 25(OH)D have been reported in a number of studies. [25][26][27][28] A large study of postmenopausal women reported 77% of women with 25(OH)D levels <28 mcg/l. 27 Deficiencies have also been noted in 78% of patients attending a UK rheumatology clinic 26 and over 90% of an Asian cohort during a UK winter.…”
Section: Introductionmentioning
confidence: 99%
“…27 Deficiencies have also been noted in 78% of patients attending a UK rheumatology clinic 26 and over 90% of an Asian cohort during a UK winter. 25 It has been widely recognised that mean 25(OH)D levels are lower in dark-skinned individuals at all ages, with greater risk of insufficiency and deficiency. [29][30][31] This racial difference is primarily due to increased melanin pigmentation which reduces UVB absorption and subsequent vitamin D production.…”
Section: Introductionmentioning
confidence: 99%